Dynamics of viral load in Crimean Congo hemorrhagic fever. Issue 4 (28th November 2017) - Hasanoglu, Imran; Guner, Rahmet; Carhan, Ahmet; K. Tufan, Zeliha; Y. Caglayik, Dilek; Yilmaz, Gul R.; Tasyaran, Mehmet A.
Abstract : Crimean Congo hemorrhagic fever (CCHF) is a viral zoonotic disease with high mortality rate. There are only a few studies on viral load in CCHF. In our study, we revealed the dynamics of viral load and its relationship with mortality in early phase of the disease. A total of 138 serum samples were collected from 23 patients. All patients had positive PCR for CCHF on admission. Serum samples were obtained daily from all patients for the first 6 days of hospitalization and stored at −80°C for viral load measurement. We found statistically significant difference between mean number of viremic serum samples of fatal and non‐fatal patients. Furthermore, non‐fatal cases' viral loads demonstrated statistically significant decreases over time; however, we could not observe a similar trend in viral loads of fatal cases. Limited number of studies on CCHF indicate that score of the contest between CCHF virus and immune system determines the survival in CCHF and viral load is found to be the most prognostic factor. In our study, we found that there is a notable decrease trend in viral loads of non‐fatal patients over time and this clearance of CCHF virus is significantly related with survival.